Septal pyogenic granuloma: a continuing riddle - Radhakrishnan, Vaishnav; Gajapathy, Sowmya; Thangaraj, Priyanka; Poduval, Jayita Das (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Pyogenic granuloma (PG) is a benign vascular lesion of the skin and mucous membranes commonly affecting the head and neck but less common in the nasal septum. Septal PG and can present with epistaxis and nasal obstruction. It is also called a lobular capillary hemangiomas (LCH) as histologically, pyogenic granuloma consists of circumscribed aggregates of capillaries arranged in lobules. Granulomatous lesions like Wegners granulomatosis, sarcoidosis and also tumours like squamous cell carcinoma, malignant melanoma can all mimic a septal PG. Surgical excision is the treatment of choice and diagnosis can be confirmed by histopathological examination. Complete resection can decrease the rates of recurrence. Here we reported a case of pyogenic granuloma of the nasal septum in a young female patient.